Examining Profiles of Poverty by Race in America: Policy Implications of a Multi-Dimensional Measure. Issue 2 (4th May 2022) - Jacob, Anupama
ABSTRACT: A looming question for U.S. social policy is whether the over 50-year old federal poverty measure paints an accurate picture of the poor in America today. A panel of experts from the National Academy of Sciences (NAS), commissioned by Congress to address the key shortcomings of the federal measure, proposed an alternative poverty measure in the early 1990s that laid the groundwork for the Supplemental Poverty Measure adopted in 2010. However, while, internationally, poverty scholars have argued that poverty is more aptly understood as a constellation of deprivations – a multi-dimensional concept, U.S. poverty measurement continues to focus on economic deprivation. Amartya Sen's groundbreaking capability approach that focuses on individuals' capacities provides the framework for the author-created multi-dimensional poverty index encompassing three dimensions Sen considers intrinsically valuable capabilities: education, health, and living standard. Drawing on publically available secondary data, this study adopts a comparative framework to examine national-level racial differences in profiles of poverty, pre-and post-the Great Recession (2005–2010), based on the federal poverty measure, the NAS measure, and the proposed multi-dimensional measure. This multi-dimensional perspective thus offers insights into the type of capability disadvantages contributing to poverty among the citizenry by race.